Simulation of optical reflectivity of single and multilayer coatings at 1064nm - Wong, Jason. (2009)
This report documents on the understanding, development and the analysis of the simulation of optical reflectivity of single and multilayer coatings at 1064nm. This project uses Essential Macleod software to simulate the reflectivity of single and multilayer thin films. High reflectance (HR) and anti-reflection (AR) coatings will be applied on various substrates such as Fused Silica and Yttrium Aluminum Garnet (YAG, Y3Al5O12) crystal. The coating materials of interest for HR and AR are Titanium, Titanium Oxide, Silicon and Silicon Oxide. The target is to achieve an optical reflection of >99.9% for HR coating and <0.2% for AR coating at 1064nm. The bandwidth of both AR and HR coatings should encompass +/-50nm from the target wavelength of 1064nm, i.e. 100nm bandwidth.